Evaluation model of reinforcement structures of Small mass movement (Sustainability in Debate, 2015)
Mass movements can be the result of elevated precipitation events and inadequate policies of land use. This study aims at diagnosing the performance of a hillside stabilization structure that suffered a landslide in the meteorological event at the Itajaí Valley in 2008, and to propose a simple method for evaluating reinforcement structures of small mass movement. The study area is located at BR”“470 ”“ km 45, near to the city limit of Gaspar and Blumenau, in Santa Catarina, South Brazil. Tests were performed to determine the infiltration rate and soil moisture, as well as a survey of the floristic composition and slope. The mass movement still takes place and the stabilization structure is compromised. The use of gabion wall and other geotechnical techniques for environmental recovery were insufficient to provide the hillside stabilization. To a greater efficiency we suggest: slope reduction; soil compaction; suitable planting species (ecologic succession); and implementation of a comprehensive drainage system.